THE ROLE OF GAMES IN TEACHING ENGLISH IN PRIMARY SCHOOL - N. Pelevina; E. Tavolzhanova (Вестник Северо-Кавказского федерального университета, 2022)
The relevance of the research is determined by the need to develop a rational methodology for teaching foreign language vocabulary using game technologies for primary school students in institutions of supplementary education, which provides the formation of lexical skills in combination with the development of oral speech skills. The article considers different approaches to the definition of «game», as well as analyzes the purpose, functions and requirements for game technologies in the process of teaching foreign language vocabulary in institutions of supplementary education. The article presents a method of teaching English vocabulary, which includes a system of game exercises corresponding to each stage of work on a lexical unit in order to improve the efectiveness of the learning process.